Higher binding affinity of Furin to SARS-CoV-2 spike (S) protein D614G could be associated with higher SARS-CoV-2 infectivity (2020)
Objective The coronavirus disease-19 (COVID-19) pandemic has caused an exponential rise in death rates and hospitalizations. The aim of this study was to characterize the D614G mutation of SARS-CoV-2 S-protein, which may affect viral infectivity. Methods The effect of D614G mutation on the structure and thermodynamic stability of S-protein was analyzed using DynaMut and SCooP. HDOCK and PRODIGY were used to model furin protease binding to the Sprotein RARR cleavage site and calculate binding affinities. Molecular dynamic (MD) simulations were used to predict S-protein apo structure, S-protein–furin complex structure, and the free binding energy of the complex. Results The D614G mutation in the G clade of SARS-CoV-2 strains introduced structural mobility and decreased thermal stability of S-protein (ΔΔG: −0.086 kcal/mol). The mutation resulted in a stronger binding affinity (Kd = 1.6  10−8 ) to furin which may enhance S-protein cleavage. Results were corroborated by MD simulations demonstrating higher binding energy of furin to S-protein D614 mutant (−61.9 kcal/mol compared with -56.78 kcal/mol for wild-type S-protein). Conclusions The D614G mutation in the G clade induced the flexibility of S-protein, resulting in increased furin binding which may enhance S-protein cleave and infiltration of host cells. As such, SARS-CoV-2 D614G mutation may result in a more virulent strain.